2016
DOI: 10.1039/c6ra12559j
|View full text |Cite
|
Sign up to set email alerts
|

Multimetallic catalysts of RuO2–CuO–Cs2O–TiO2/SiO2for direct gas-phase epoxidation of propylene to propylene oxide

Abstract: RuO2–CuO–Cs2O–TiO2/SiO2 catalyst is highly active for the epoxidation of propylene to propylene oxide, producing 3015 gPO h−1 kgcat−1, the highest PO formation rate reported to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…11). For the TiO2/SiO2 catalyst, no clear H2 reduction peak could be seen in this temperature range, consistent with previous reports [21,22]. For Na2WO4/SiO2, a broad reduction peak starting from 450 ºC to above 900 ºC with a maximum H2 consumption at about 800 ºC was observed, indicating the reduction of W species [22].…”
Section: Characterization Of Tio2/sio2 Na2wo4/sio2 and Na2wo4-tio2/supporting
confidence: 90%
“…11). For the TiO2/SiO2 catalyst, no clear H2 reduction peak could be seen in this temperature range, consistent with previous reports [21,22]. For Na2WO4/SiO2, a broad reduction peak starting from 450 ºC to above 900 ºC with a maximum H2 consumption at about 800 ºC was observed, indicating the reduction of W species [22].…”
Section: Characterization Of Tio2/sio2 Na2wo4/sio2 and Na2wo4-tio2/supporting
confidence: 90%
“…For pure Bi 2 O 3 , the Bi 4f 5/2 and Bi 4f 7/2 peaks are observed respectively at 163.9 and 158.6 eV, 52 whereas, in the present case, these peaks (Bi 4f 5/2 and Bi 4f 7/2 ) are found to be upward-shifted to 164.9 and 159.6 eV, respectively (Figure 2e). The reported XPS peaks of Cs 3d at 725.2 eV for Cs 3d 5/2 and at 739.2 eV for Cs 3d 3/2 53,54 are observed to be downward-shifted to respective positions of 724.4 and 738.5 eV in the Cs 2 O–Bi 2 O 3 –ZnO heterostructure (Figure 2d). In short, the upward shifts observed in the positions of Zn 2p 1/2 , Zn 2p 3/2 , Bi 4f 5/2 , and Bi 4f 7/2 , and the downward shifts observed in the positions of Cs 3d 3/2 and Cs 3d 5/2 confirm that the electrons migrate from the Bi 2 O 3 CB and ZnO CB to Cs 2 O CB (Scheme S1).…”
Section: Resultsmentioning
confidence: 93%
“…For a mixed MoO 3 /Bi 2 SiO 5 catalysts supported on SiO 2 , propylene oxide selectivities of 55% were reported at a propylene conversion of 22% at 400 1C for a diluted feed with a molar ratio of O 2 /C 3 H 6 of 4 : 1, 343 whereas high formation rates of propylene oxide were observed for a RuO 2 /CuO catalyst supported on SiO 2 . 344 Using a copper-manganese mixed metal oxide catalyst, Seubsai et al 345 found selectivities 430% towards propylene oxide at up to 1.5% propylene conversion at 300 1C. These catalyst systems are structurally and chemically similar to typical chemical looping redox catalysts, indicating the potential for future work in this field.…”
Section: View Article Onlinementioning
confidence: 97%